Development of perivascular astrocyte processes - Cohen-Salmon, Martine; Guille, Naomie; Boulay, Anne-Cécile (Frontiers in Neuroscience, 2025)
Astrocytes are key glial cells in the brain that form specialized contacts with the vascular system. Together, these interactions constitute the gliovascular unit (GVU), which is an interface between the brain and the blood crucial for the maintenance of the structure and functions of the brain. The development of the GVU is a complex process involving multiple steps and intricate interactions among astrocytes, neural cells, and vascular components. In this review, we aim to summarize the current understanding of the development of the astrocyte–vascular interface and to explore how early developmental alterations in this system may contribute to brain dysfunction.